Enfrentando o establishment : partidos desafiantes de esquerda na América Latina - Leonardo da Silveira Ev (2020)
Throughout the years 2000 and 2010, Latin America saw the emergence of several parties of the left that managed to reach the National Executive of their countries. The so-called "pink tide" has been the object of extensive study with various explanations for the success of leftist parties. This research is explores a still unknown perspective, that is, framing the Latin American left as the challenger of the party establishment. The study analyzes cases of success and failure, relating the different performances to the institutionalization and the development of party resources by the selected challenger parties of in the continent